Pemanfaatan Limbah Sampah Plastik Menjadi Taman Ecobrick Melalui Metode Participatory Action Research Di Desa Tambak Lekok Kabupaten Pasuruan - Sulistyowati , Enik; Zulkif , Senjaya Machfudi; Sofiyulloh, Sofiyulloh; Azis , Abd.; Hendratama , Handik; Riyana, Iis; Hamida , Nur (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The aim of this service activity is to provide understanding to the community to care about the environment, to provide an understanding of the negative and positive impacts of throwing rubbish carelessly, to provide positive motivation to the people of Tambak Lekok that plastic waste can not only be disturbing waste, but can be utilized and processed into Economic goods include decorative products using the ecobrick process and ecobrick gardens. The method used to achieve this PKM goal is through lectures and training in the form of workshops. Training-related materials are delivered through lectures, discussions and direct practice. Next, evaluate the results by checking the results of the ecobricks that have been made and the ecobrick park. Overall, this PKM activity has had good and satisfying results, this is demonstrated by the creation of an ecobrick park right in the skylot tourist area in Tambak Lekok Village which can be used as a photo spot and playground during school breaks